Ciclo de orientação a familiares de idosos dependentes: uma experiência da prática profissional do assistente social na educação para os cuidados de idosos - Oliveira, Ilka Custódio de (2008)
This paper brings together the professional experience of social workers in a program for elderly caregiving education. The program is titled COFID (Counseling Program for Families of Dependent Elderly) and was carried out between 2004 and 2006 by the Vida Baureri Group, a non-profit organization located in the Greater São Paulo Metropolitan Area, Brazil, which is geared to the needs of elderly patients. COFID is an education training program whose main purpose is to provide family caregivers with the necessary tools to assist dependent elderly patients in their everyday activities and serve as a space for exchange of experiences on caregiving and building the caregiver s identity. This theme has become increasingly relevant in Brazil over the years due to the Brazilian population s rapid aging process, which may be characterized as a new manifestation of social issues when perceived as one of the various forms of social exclusion. This corroborates the social workers activity as they are faced with new challenges and demands. Furthermore, the legislation concerning the elderly in Brazil enforces that families should be responsible for the elderly person s care without, however, ensuring the necessary conditions for complying with this legal requirement